PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU PNS DI SMA NEGERI RAYON II ( RAYON BREBES BARAT ) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examined the role of Principal Leadership Moderating Effect of Professional Competence and Motivation Work Against Teacher Performance PNS in SMA Rayon II (Rayon Brebes West). The purpose of this study was to examine how the role of Principal Leadership Moderating Effect of Professional Competence and Motivation Work Against Teacher Performance PNS in SMA rayon Brebes west. The sample in this study were 98 respondents, which amount is taken under the provisions of Slovin from a population of 130 government school teachers in SMA rayon Brebes west. In this study, using primary data obtained by questionnaire. The method of data analysis used linear regression to test moderation The results showed professional competence have positive and significant impact on teacher performance, motivation does not work and does not have a significant effect on the performance of teachers. School leadership does not have a significant effect on the performance and not the teacher. The influence of moderation between the leadership of the principal of the relationship between professional competence in the performance of teachers. There is no moderating effect between school leadership on the relationship between teachers' work motivation and performance. Key words: Professional competence, motivation, teacher performance, and moderation of school leadership